Drogheda as a case study of Anglo-Norman town foundation in Ireland, 1194-1412 - Buldorini, Chiara (Trinity College (Dublin, Ireland). Department of History, 2010)
This case study addresses the foundation and evolution of Drogheda’s civic government as revealed by forty-five charters and other ancillary grants bestowed on the town from 1194 to 1412. This source material will throw light on the pattern of transmission of Anglo-Norman municipal law to Ireland and on customary law of the Irish borough/town. Charters hold the key to a better understanding of Drogheda’s internal administration, relationship with the central and local government and commercial functions. Charters are evaluated as a manifestation of institutional and cultural dissemination in a colonial context as well as products of contextual politics. By the same token, their chronologies and list of witnesses and political backgrounds are exploited as a source for a interpretation of Anglo-Irish relations from the late-twelfth to the early-fifteenth centuries.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin